2002
DOI: 10.2172/15000693
|View full text |Cite
|
Sign up to set email alerts
|

Avian Hearing and the Avoidance of Wind Turbines

Abstract: This report provides a complete summary of what is known about basic hearing capabilities in birds in relation to the characteristics of noise generated by wind turbines. It is a review of existing data on bird hearing with some preliminary estimates of environmental noise and wind turbine noise at Altamont Pass, California, in the summer of 1999. It is intended as a resource in future discussions of the role that hearing might play in bird avoidance of turbines. The main body of this report describes hearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 49 publications
2
46
0
Order By: Relevance
“…In contrast to many other man-made sounds, traffic sound is relatively easy to characterize and measure. Moreover, birds present an interesting animal model to examine these effects because their vocal and auditory behavior is relatively easy to study in both the laboratory and the field, resulting in a large database from which to base estimates (Dooling et al, 2000a;Dooling, 2002). A report in 2007 for the California Department of Transportation (CALTRANS) comprehensively reviewed the literature on the effects of traffic noise on birds, documented the complexity of the problem, identified issues that were adequately addressed by existing science, and highlighted other issues that at the time could not be resolved (Dooling and Popper, 2007).…”
Section: Review Of the Literature Up To 2007mentioning
confidence: 99%
“…In contrast to many other man-made sounds, traffic sound is relatively easy to characterize and measure. Moreover, birds present an interesting animal model to examine these effects because their vocal and auditory behavior is relatively easy to study in both the laboratory and the field, resulting in a large database from which to base estimates (Dooling et al, 2000a;Dooling, 2002). A report in 2007 for the California Department of Transportation (CALTRANS) comprehensively reviewed the literature on the effects of traffic noise on birds, documented the complexity of the problem, identified issues that were adequately addressed by existing science, and highlighted other issues that at the time could not be resolved (Dooling and Popper, 2007).…”
Section: Review Of the Literature Up To 2007mentioning
confidence: 99%
“…Most studies of auditory warning devices have found that birds become habituated to these devices. Birds do not hear as well as humans (Dooling 2002), and minor modifications to the acoustic signature of a turbine blade could make blades more audible to birds, while at the same time making no measurable contribution to overall noise level. Under certain conditions (e.g., high wind), birds might lose their ability to see a turbine blade before they are close enough to hear the blade.…”
Section: B Turbine Characteristics and Locationmentioning
confidence: 99%
“…In addition, data on the auditory sensitivity of the lesser scaup will add to current literature on comparative avian hearing. Of the approximately 10 000 extant species of birds, hearing has only been measured in about 50 species (Dooling et al, 2000;Dooling, 2002). Approximately half of all birds for which there are hearing data are from the order Passeriformes (perching birds-includes the songbirds), as well as 13 species of owl and several other non-passerine, non-aquatic birds (Dooling et al, 2000;Dooling, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Of the approximately 10 000 extant species of birds, hearing has only been measured in about 50 species (Dooling et al, 2000;Dooling, 2002). Approximately half of all birds for which there are hearing data are from the order Passeriformes (perching birds-includes the songbirds), as well as 13 species of owl and several other non-passerine, non-aquatic birds (Dooling et al, 2000;Dooling, 2002). There are few data on aquatic birds, with only the blackfooted penguin (Spheniscus demersus, Wever et al, 1969) and the mallard duck (Anas platyrhynchos, Trainer, 1946) represented in the literature.…”
Section: Introductionmentioning
confidence: 99%